JÓZEF MACKIEWICZ AND SECTS - Pełczyński, Grzegorz (Porównania, 2012)
The article is dedicated to a part of early reportage work of Józef Mackiewicz. In the reportages written at the end of 1930s, he presented Protestant religious minorities which back then flourished in eastern part of Poland, but which did not have a positive opinion among the authorities and other peoples. Mackiewicz stated that all the accusations towards those sects were groundless. He also claimed that they can positively influence social relations. Mackiewicz’s reportages on sects was an isolated case of interest in this topic in Poland of those times.